Implementasi Corporate Social Responsibility (CSR) PT. Nusa Halmahera Minerals Dalam Pemberdayaan Pendidikan di Kecamatan Kao Kabupaten Halmahera Utara - BUBALA, EFENDI; Pesoth, Willy Ferdinan; Kiyai, Burhanudin (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : The aim of research to determine the Implementation of Corporate SocialResponsibility (CSR) PT. Nusa Halmahera Minerals (NHM) in the empowerment ofEducation in District Kao North Halmahera. According to the Limited Liability CompanyAct No. 40 2007 Article 74, paragraph 1 states that the limited liability company doingbusiness in the field or concerned with natural resources required to run a social andenvironmental responsibility. Then in Act No. 25 of 2007 article 15 part (b) states that eachinvestment shall implement corporate responsibility. PT. Nusa Halmahera Minerals hasinitiated programs in various fields, one of them in the field of educational empowerment inthe area around the mine in particular in the sub Kao consisting of 14 village is in the formof scholarships for students who are still active college instituted tingggi. But its realizationuntil now not in accordance with the expectations of the community around the mine due tothe disbursement of the scholarship fund is not timely. Even in the implementation of CSRprogram PT. Nusa Halmahera Minerals in the empowerment of education in District Kaolack of supervision of direct supervisor, lack of communication between the CSR and thegovernment district as well as the community as a group of recipients.Keywords: Implementation of Corporate Social Responsibility PT. Nusa HalmaheraMinerals In Empowerment Education in District Kao North Halmahera.